2007
DOI: 10.1007/s10616-007-9103-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-fucosylated therapeutic antibodies: the next generation of therapeutic antibodies

Abstract: Therapeutic antibody IgG1 has two N-linked oligosaccharide chains bound to the Fc region. The oligosaccharides are of the complex biantennary type, composed of a trimannosyl core structure with the presence or absence of core fucose, bisecting N-acetylglucosamine (GlcNAc), galactose, and terminal sialic acid, which gives rise to structural heterogeneity. Both human serum IgG and therapeutic antibodies are well known to be heavily fucosylated. Recently, antibody-dependent cellular cytotoxicity (ADCC), a lytic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…However, these methods can be expensive, and to reduce the overall cost of therapeutic MAbs, several approaches have been tried to upgrade the efficacy per unit dose. For example, antibodies lacking fucose can be produced in a-1, 6-fucosyltransferase (FUT8) knockout Chinese hamster ovary (CHO) cell lines (POTELLIGENT TM technology) and have been reported to show higher antibodydependent cellular cytotoxicity (ADCC) (Mori et al 2007;Shields et al 2002;Shinkawa et al 2003). In addition, use of larger scale production facilities can reduce the cost per unit weight, and tanks are now available that contain more than 10,000 L of culture medium (Birch and Racher 2006;Brian 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods can be expensive, and to reduce the overall cost of therapeutic MAbs, several approaches have been tried to upgrade the efficacy per unit dose. For example, antibodies lacking fucose can be produced in a-1, 6-fucosyltransferase (FUT8) knockout Chinese hamster ovary (CHO) cell lines (POTELLIGENT TM technology) and have been reported to show higher antibodydependent cellular cytotoxicity (ADCC) (Mori et al 2007;Shields et al 2002;Shinkawa et al 2003). In addition, use of larger scale production facilities can reduce the cost per unit weight, and tanks are now available that contain more than 10,000 L of culture medium (Birch and Racher 2006;Brian 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the complex structure with fucosylated Fc, these contacts are weakened or nonexistent (Ferrara et al, 2011). Although afucosylated IgGs exist naturally, a next generation of recombinant therapeutic, glycoenginereed antibodies with enhanced ADCC activity is currently being developed for better efficacy (Mori et al, 2007;Ysebaert et al, 2010;Robak and Robak, 2011).…”
Section: Afucosylated Antibody Has Enhanced Adcc and Can Translate Inmentioning
confidence: 99%
“…Preclinical studies have shown that antibody dependant cell-mediated cytotoxicity (ADCC) is an important part of mechanism of action of therapeutic monoclonal antibodies, especially anti-cancer antibodies, such as Trastumab and Rituximab against tumors (Mori et al, 2007). Some clinical evidence based on genetic analysis of leukocyte receptor (Fc R) polymorphisms of cancer patients treated with anti-CD20 IgG1 Rituximab and anti-HER2 IgG1 Trastuzumab therapies has revealed that ADCC is one of the critical mechanisms responsible for the clinical efficacy of these therapeutic antibodies (Musolino et al, 2008;Kim et al, 2006;Cartron et al, 2002).…”
Section: Antibody Produced By Glycoengineered Pichia Has Better Efficacymentioning
confidence: 99%
“…It is not surprising that increasing effector functions by means of Fc-glycosylation engineering has gained considerable interest 196 . As a consequence, the pharmaceutical industry has allocated remarkable research efforts to glycan engineering, aiming to increase ADCC of mAbs, in particular by limiting core fucosylation 48,65,91,[308][309][310][311][312][313] . Many reports have described the significant increase of ADCC whenever the fucose attachment to the glycan backbone was precluded 42,196,308,312 .…”
Section: Introductionmentioning
confidence: 99%